Influence Support Social and Gratitude To Optimism Through the Hardiness of Mothers Who Have Children with Needs Special - Setyaningsih, Ariyanti; Virgonita, Mulya (Sahabat Publikasi, 2024)
This study aims to analyze the relationship between social support, gratitude, and resilience to optimism in mothers of children with special needs. This study used a sample of 50 respondents selected through purposive sampling. The validity of the sample was tested using the loading factor and the average variance extracted (AVE), while the reliability was tested using internal consistency based on Cronbach's Alpha and Composite Reliability. The results of the validity test showed valid values for the loading factor and AVE, and the results of the reliability test showed that the Cronbach's Alpha and Composite Reliability values met the criteria. The results of the study revealed that social support had a significant positive effect on optimism, with a beta coefficient value of 0.390 and a T-Statistics of 2.570. Gratitude also had a significant positive effect on optimism, with a beta coefficient value of 0.169 and a T-Statistics of 0.992. However, social support did not have a significant effect on resilience, with a beta coefficient value of -0.217 and a T-Statistics of 1.282. In contrast, gratitude has a significant positive effect on resilience, with a beta coefficient value of 0.552 and a T-Statistics of 5.389. In addition, resilience has a significant positive effect on optimism, with a beta coefficient value of 0.206 and a T-Statistics of 1.346. Social support also significantly affects optimism through resilience as an intervening variable, with a beta coefficient value of 0.244 and a T-Statistics of 1.489. However, gratitude does not significantly affect optimism through resilience, with a beta coefficient value of -0.262 and a T-Statistics of 2.060.